RAIE : Des représentations spatiales à l’aide à la décision participative pour la localisation de sites - Éric Masson; Jean-Baptiste Litot; Edwige Motte; Olivier Blanpain (M@ppemonde)
This article presents a tool developed to enable spatialized decision support and GIS-assisted cartography. Called RAIE (Repulsion, Attraction, Inclusion, Exclusion), this tool allows an interviewee or a group, during interviews, to produce maps in a GIS from a declarative ontology. Showing the challenges and spatial constraints of different actors for the location of a strategic site, RAIE also provides a common database of geographic data and map production, contributing to a spatialized multicriteria decision.